High precision and selectivity for quantitation of enrofloxacin and ciprofloxacin in five chicken tissues using solid phase extraction and ESI LC-MS/MS for application in monitoring residues - Ferrari, Sarita Priscila Gobbo [UNESP]; Bonassa, Karina Parra Duarte; Coelho, Mirela Batista; Ferreira, Christina Ramires; Costa, Heni Falcao da [UNESP]; Jara, Jose Luis Paz; Miguel, Maria Carolina Villani [UNESP]; Reyes, Felix Guillermo Reyes; Eberlin, Marcos Nogueira; Nogueira, Guilherme de Paula [UNESP]; Simas, Rosineide Costa [UNESP] (Royal Soc Chemistry, 2015)
Fluoroquinolones (FQs) are synthetic antimicrobials commonly used in intensive poultry farming to treat chronic respiratory disease, colibacillosis, and fowl cholera. As these drugs are also important in treating infections in humans, their use in poultry has been restricted in some countries to avoid the development of antimicrobial-resistant bacteria. In this work, a novel simple and efficient LC-MS/MS method using solid phase extraction (SPE), ESI ionization and multiple reaction mode (MRM) has been developed and validated to determine the two most common FQ residues: enrofloxacin (ENR) and ciprofloxacin (CIP) in chicken target tissues (muscle, liver, kidney, fat and skin) and in plasma. The method is shown to be sensitive, with limits of quantification (LOQ) between 1 ng g(-1) and 5 ng g(-1), recoveries 93-115% and correlation coefficients greater than 0.99. This novel methodology allows faster and simpler sample workflow compared to previously reported methodologies, making it ideal for high-throughput screening and confirmation of both ENR and CIP meeting the international regulation levels.